Electric field effect on elastic properties of uniaxial relaxor SrxBa1−xNb2O6 single crystals with strong random fields. (26th September 2017) - Aftabuzzaman, Md; Al Helal, Md; Dec, Jan; Kleemann, Wolfgang; Kojima, Seiji
Abstract: The elastic properties of uniaxial relaxor Sr x Ba1− x Nb2 O6 ( x = 0.70, SBN70) single crystals with strong random fields (RFs) were studied by Brillouin scattering spectroscopy as functions of temperature and external electric field along the [001] direction. A remarkable diffuseness of a ferroelectric phase transition was observed both on zero field heating and zero field cooling. The analysis of elastic anomaly shows the stretched critical slowing down of polar nanoregions (PNRs). Under 3.0 kV/cm, a complete alignment of nanodomains and an enhancement of the long-range ferroelectric order were observed below the Curie temperature T C = 23 °C. The alignment of quasistatic PNRs above T C was also observed under a sufficiently strong electric field. In a field-dependent measurement, a mixed state consisting of field-induced macrodomains and nanodomains caused by RFs was observed at 3.4 kV/cm. This mixed state persisted up to 9.0 kV/cm due to the incomplete switching of nanodomains to the macro/single domain state.